A Educação Física inclusiva no ambiente escolar em Centenário/TO - Brito, Ida Costa (Universidade Federal do Tocantins, 2021)
This monograph aims to know and analyze how the inclusion of students with physical disabilities occurs in classrooms and in the school environment in Centenário / TO, focusing mainly on physical education classes, their difficulties and advances. Initially, to contextualize the theme, a historical rescue was carried out regarding the importance of the legislation on Special Education and the inclusion of students with disabilities in classes, thus guaranteeing their rights in important guiding documents, Public Policies and laws, that is, the legal protection that all students with special needs have the right to be included in school activities in all subjects of the school curriculum. To conclude, we highlight that the inclusion of people with special needs and physical disabilities in school can be beneficial as a form of school adaptation, for students with special needs, with the presence of the Physical Education teacher as a mediator of this process.